Zapisz w postaci jednej potęgi

A) 13^5*13^6

B) (-123)^3*(-123)^9

C) 6^11*6*6^12

D) (-17)^9/(-17)^4

E) 1 1/3^13/1 1/3

F) 8^14*8^16/8^15

G)a^5*(-a)

H) (-z)^7*z/z²

I) z^7*(-x)^5/(-x)^3



Odpowiedź :

Odpowiedź:

A)

13^5 * 13^6 = 13^11

B)

(-123)^3 * (-123)^9 = (-123)^12

C)

6^11 * 6 * 6^12 = 6^12 * 6^12 = 6^12

D)

(-17)^9/(-17)^4 = (-17)^5

E)

(1 1/3)^13/(1 1/3) = (1 1/3)^12

F)

8^14 * 8^16/8^15 = 8^14 * 8^1 = 8^15

G)

a^5 * (-a) = ^-a^6

H)

(-z)^7 * z/z² = -z^7 : z = -z^6

I)

z^7 * (-x)^5/(-x)^3 = z^7 * (-x)² = x²z^7



Szczegółowe wyjaśnienie:



Szczegółowe wyjaśnienie: